Psychiatric symptoms in myoclonus-dystonia syndrome are just concomitant features regardless of the SGCE gene mutation. (September 2017) - Kim, Ji-Young; Lee, Woong-Woo; Shin, Chae Won; Kim, Han-Joon; Park, Sung-Sup; Chung, Sun Ju; Cho, Jin Whan; Ryu, Ho-Sung; Son, Tae Ok; Jeon, Beomseok
Abstract: Introduction: Among myoclonus-dystonia syndrome (MD) patients, psychiatric disorders including depression, anxiety, alcohol dependence, obsessive-compulsive disorder (OCD) and panic disorder have been frequently reported to be related with the epsilon-sarcoglycan gene ( SGCE ) mutation. However, the rate of psychiatric disorders has not been compared between MD patients with the SGCE mutation ( SGCE (+)) and without the SGCE mutation ( SGCE (−)). We analyzed the psychiatric data in both SGCE (+) and SGCE (−) MD patients to determine the association of the SGCE mutation with psychiatric disorders in MD. Methods: Twenty-six MD patients who fulfilled the Grunewald's criteria and underwent a SGCE gene study were enrolled. Patients were divided into two groups according to their SGCE status ( SGCE (+) and SGCE (−) group). They were systematically assessed using a standardized protocol including motor severity scales and psychiatric questionnaires for depression, anxiety, alcohol dependence, OCD and panic disorder. Results: Fifteen SGCE (+) and eleven SGCE (−) patients were enrolled. Mean age at onset, disease duration, family history, alcohol responsiveness and motor severity were not different between the SGCE (+) and SGCE (−) group. Although more than half (53.8%) of all the MD patients had psychiatric symptoms, there were no significant differences between the SGCE (+) and SGCE (−) group in terms of their psychiatric questionnaire scores and rate of psychiatric disorders. Conclusions: Psychiatric features are not likely to be related with the SGCE mutation itself but just bespeak disability in clinical MD syndrome regardless of the SGCE mutation. Highlights: Psychiatric disorders were frequently reported as accompanying features in SGCE (+) MD. Frequencies of psychiatric disorders (depression, anxiety, alcohol dependence, OCD, and panic disorders) were compared between SGCE (+) and SGCE (−) MD. There were no differences in frequencies of psychiatric disorders between SGCE (+) and SGCE (−) MD. Psychiatric disorders in MD are not likely to be related with SGCE mutation.